Evaluation Of Category III Overhead Tools Inspection Rig X PT. BMS - Suranta, Bambang Yudho; Rahman, Muhammad Hafiz; Sofyan, Akhmad (Jurnal Polimesin, 2024)
Overhead tool inspection is an important process in the oil and gas well drilling and maintenance industry. In harsh and hazardous environments, it is important to regularly monitor the physical condition and functionality of overhead tools. The use of overhead tools in the oil and gas industry has the advantage of lifting and moving heavy loads easily and safely. However, the use of heavy equipment also carries the risk of dangerous work accidents. The methodology in this research involves problem identification, literature review, research design, data collection, interpretation, analysis, and findings. The discussion emphasizes the meticulous inspection required for overhead tools, exemplified through the evaluation of traveling block, hook block, crown block, elevators, and elevator links. Each inspection, guided by API standards, ensures compliance, identifies potential hazards and prevents incidents in the inspection of overhead tools, various methods are used to ensure accurate inspection results and reduce the risk of failure during operation. This inspection involves techniques such as visual inspection and Non-Destructive Test (NDT) to test each overhead tools component which is guided by API SPEC 8A, API RP 8B and also API SPEC 8C. The main objective is to ensure that every aspect of the overhead tools has been carefully inspected and produces accurate inspection results. Thus, the risk of failure when inspecting overhead tools can be significantly reduced.The results indicate that the overhead tools inspected at PT. BSM meets API SPEC 8C standards. However, crucial findings, such as defects in crown block bearings and elevator safety pin issues, underscore the need for immediate attention. The conclusion emphasizes the importance of swift action to maintain safety and prevent further damage.